Molecular identification and diversity of adult arthropod carrion community collected from pig and sheep carcasses within the same locality during different stages of decomposition in the KwaZulu-Natal province of South Africa - Danisile Tembe (PeerJ Inc., 2021)
The current study aimed at molecular identification and comparing the diversity of arthropods communities between pig and sheep carcasses during the cold and warm season in KwaZulu-Natal province of South Africa. Adult arthropods found on and around the carcasses were collected using either fly traps or forceps. Molecular analyses confirmed the identification of twelve arthropod species collected from both sheep and pig carcasses during the cold season. Results showed that 11 of 12 arthropod species were common in both sheep and pig carcasses, with exception to Onthophagus vacca (Coleoptera: Scarabaeidae) (Linnaeus, 1767) and Atherigona soccata (Diptera: Muscidae) (Rondani, 1871) species which were unique to sheep and pig carcasses respectively. However, during the warm season, the sheep carcass attracted more arthropod (n = 13) species as compared to the pig carcass. The difference in the obtained arthropod was due to the presence of O. vacca which was also unique to the sheep carcass during this season. Furthermore, there was an addition of a beetle species Hycleus lunatus (Coleoptera: Meloidae) (Pallas, 1782), which was collected from both sheep and pig carcasses but unique to the warm season. The pig carcass attracted more dipteran flies during both warm (n = 1,519) and cold season (n = 779) as compared to sheep carcass during the warm (n = 511) and cold season (n = 229). In contrast, coleopterans were more abundant on the sheep carcass during the warm season (n = 391) and cold season (n = 135) as compared to the pig carcass in both warm season (n = 261) and cold season (n = 114). In overall, more flies and beetles were collected on both sheep and pig carcasses during the warm season, and this further highlight that temperature influenced the observed difference in the abundance of collected arthropod between seasons.